Comparison of PaO2/FiO2 ratio with SpO2/FiO2 ratio in Respiratory Failure patients - Srinivasan, Darshni; Mathivanan, Koushik Muthu Raja; Thangaswamy, Dhanasekar (Journal of Neonatal Surgery, 2025)
Background: Respiratory failure is marked by inadequate oxygen delivery to tissue or insufficient carbon dioxide removal, commonly categorized into type 1 (hypoxemia) and type 2 (hypercapnia) respiratory failure. The diagnostic criteria for acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) rely on the PaO2/FiO2 (P/F) ratio obtained through arterial blood gas (ABG) analysis to evaluate the severity of hypoxemia. We hypothesized that pulse oximetry saturation SpO2/FiO2 (S/F) ratio could serve as an alternative to the P/F ratio for assessing the oxygenation parameters associated with ALI. Methods: This periodic observational study included 59 patients with acute respiratory failure. This study aimed to assess the sensitivity and specificity of the S/F ratio as a surrogate for the P/F ratio in diagnosing ALI and ARDS. FiO2, SpO2 and PaO2 levels were recorded at five-minute intervals, and the relationship between S/F and P/F ratios was analyzed using linear regression and receiver operating characteristics (ROC) curves. Results: There is a significant positive correlation between S/F and P/F ratios, with a linear regression equation of S/F = 183.819 + 0.299 + P/F (r=0.607). For diagnosing cut-off of 272 yielded a sensitivity of 77.3% and specificity of 80%, while for ARDs an S/F cut-off of 247 showed a sensitivity of 69.6% and specificity of 83%. The ROC curve analysis indicated good discrimination abilities for both ARDS (AUC = 0.764) and ALI (AUC=0.786) using the S/F ratio. Conclusion: S/F ratio provides an alternative for assessing oxygenation and diagnosing ALI and ARDS.